The Change of the Performance Style of a Fiddler from the Gyimes Region Depending on the Collecting Situations - Veronika Pásku (Muzikološki Zbornik, 2025)
János Zerkula (1927–2008) was an unavoidable figure of the folk music of the Gyimes region and the Hungarian dance house movement. Since the 1960s, numerous folk music researchers, and enthusiastic folk music lovers recorded him. The study examines how different collection situations have influenced his performance style.